Advances in athlete genomics in 2019 - Szalata, Marlena; Słomski, Ryszard; Balkó, Štefan; Balkó, Iva (Akademia Wychowania Fizycznego w Poznaniu)
A literature search revealed that more than 120 genetic markers seemed to be linked to athletic performance. Among them endurance markers: ACTN3 577X, PPARA rs4253778 G, PPARGC1A Gly482 and most widely studied ACE I; power/strength markers: ACTN3 Arg577, AMPD1 Gln12, HIF1A582Ser, MTHFR rs1801131 C, NOS3 rs2070744 T, PPARG 12Ala and most widely studied ACE D can be taken into consideration as showing positive associations with athlete status. However the genetic architecture of athletic performance seemed to be still the most important challenge and necessary step to full understanding of the background of talent identification both in sport as in dance and other related abilities associated with body movement. On the other hand, the significance of some genetic markers has not been replicated in more than one study.
Keywords: athlete; genetic markers; endurance; power/strenght